MANAGEMENT AND DEVELOPMENT OF A RESIDENTIAL ENERGY STORAGE SYSTEM: A CASE STUDY JORDAN - Abu-Attieh, Sameera; Al-Omari, Zakaria; Emar, Walid (Journal of Applied Engineering Science, 2022)
The use of renewable energy generation (REG) and energy storage systems (ESSs) strategies have a considerable possibility in delivering resilience for renewable energy sources (RESs). Thus, combining REG and ESSs strategies to fix operational, economic, ecological, and power-concerning governmental issues have been received particular concern from power system (PS) operators and planners globally. In this concern, developing countries (Jordan), which are poor in traditional energy resources, have proposed different supportive issues and experiences for the common use of ESSs strategies in the situation of distribution PSs. Therefore, this article performs a universal solution to this problem possessed to construct the infrastructure substantially to achieve high penetration of RE in the PS. Based on this, the article firstly studies the necessity of using REG and ESSs strategies in RE-based distribution PS. So, the current approaches and motivation programs used in various countries for the growth of RERs in optimum composition with ESSs and REG strategies are offered. The results of this study suggest that the use of an ESS is very important for the management and development of residential Solar Energy (SE) applications. Most respondents (85.3%) said that the use of a domestic ESS is critical to the management and growth of demand and supply for RE. To improve main grid efficiency and reduce demand for conventional power supplies, Jordanian engineers and experts recommend that consumers should install ES devices in their homes.